MEMBANGUN LOYALTY TOWARD BRAND PADA SHOPEE: PERAN PERCEIVED ENJOYMENT DAN SUBJECTIVE NORM - Oliandes Sondakh; Renna Magdalena; Arvin Gunawan (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
The development of e-commerce platforms not only focuses on transaction activities but also presents entertainment features such as digital games to increase user engagement. One such feature is Shopee Games, which is designed to provide an interactive experience for users. This study aims to analyze the influence of Perceived Enjoyment and Subjective Norm on Attitude toward Brand and its implications for Loyalty toward Brand among Shopee Games users. This study uses a quantitative approach with a survey method of 99 respondents who are Shopee Games users. The data analysis technique was carried out using Partial Least Squares - Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results show that Subjective Norm has a positive effect on Attitude toward Brand, while Perceived Enjoyment has no significant effect on Attitude toward Brand. In addition, Attitude toward Brand is proven to have a positive influence on Loyalty toward Brand. These findings indicate that social influence has an important role in shaping user attitudes towards Shopee, which ultimately can increase brand loyalty. This study implies that companies need to strengthen community-based marketing strategies and social influence to increase user loyalty towards game features in e-commerce platforms.